Property investment - Isaac, David; O'Leary, John (Palgrave Macmillan, 2011)
With a focus on strategies for investment, markets and appraisal, this new edition explores the response of property investment markets to the challenges of sustainability, and provides expanded coverage of both residential and commercial property investment. There is new discussion on investment vehicles such as real estate investment trusts